"It Could Be Better" Can Make It Worse: When and Why People Mistakenly Communicate Upward Counterfactual Information. (April 2023) - Li, Xilin; Hsee, Christopher K.; O'Brien, Ed
Imagine you are a real estate agent and are showing a prospective buyer a house with a lake view, but it is foggy, and the view is less than ideal. Are you inclined to tell the prospective buyer, "Unfortunately, it is foggy outside. If it were not foggy, the view would be even better!"? Eight studies, spanning diverse domains, reveal a novel discrepancy: most presenters (e.g., the seller) choose to communicate such upward counterfactual information (UCI) to experiencers (e.g., the prospective buyer), believing it will enhance experiencers' impressions (e.g., of the house)—yet UCI actually worsens their impressions. This discrepancy arises because presenters insufficiently account for the fact that they possess more knowledge about the presented target than experiencers do; they fail to realize that noting an imperfection reveals it. Accordingly, when experiencers are knowledgeable about the target, either because the imperfection is obvious or because they can easily envision the upward counterfactual, the discrepancy attenuates. Finally, the presenter–experiencer discrepancy occurs only when the counterfactual information is upward, such that presenters do not overcommunicate downward counterfactual information, which rules out a desire to share any information as an alternative mechanism for presenters' communication decisions. Together, this research highlights the prevalence and costs of sharing UCI.